LIDOCAINE - HSA BINDING CHARACTERIZED BY FLUORESCENCE SPECTROSCOPY AND MOLECULAR DOCKING - NEAMTU, S.; BUIMAGA-IARINCA, L.; BOGDAN, M.; TURCU, I. (Studia Universitatis Babeș-Bolyai Physica, 2016)
Quenching fluorescence and molecular docking methods were used to evaluate changes in the local environment of intrinsic fluorophores of HSA in the presence of lidocaine and to calculate the binding parameters that characterize drug-protein interaction. We show that lidocaine induces significant fluorescence quenching of tryptophan and changes in conformation of IIA domain of HSA. The bimolecular quenching rate constant calculated using Stern-Volmer equation indicates a direct binding as the cause of fluorescence quenching. The protein-ligand association constant determined from Trp fluorescence quenching data showed a weak binding of lidocaine to HSA. The molecular docking calculations indicates three docking sites for lidocaine, in IIIA and IIA and IB domains of HSA, with preference for cavities located in IIIA.